1985
DOI: 10.1037/0278-6133.4.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic risk assessment in primary breast cancer by behavioral and immunological parameters.

Abstract: Although findings from recent animal studies suggest that behavioral factors such as "helplessness" play a role in cancer progression, very few such studies with humans have been carried out. The study investigated the predictive power of an immunologic effector cell, the natural killer (NK) cell, as well as selected psychological and demographic factors, to breast cancer prognostic risk status. It was found that NK activity predicted the status of cancer spread to the axillary lymph nodes. Patients who had lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
88
0
12

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(108 citation statements)
references
References 18 publications
8
88
0
12
Order By: Relevance
“…21,37 Although the association between impaired NCA and the development of breast cancer has not been established, research on humans and other species points to a significant role of NCA in preventing the development of cancer, including breast cancer, and its metastases. [1][2][3][4]8,9 Additional studies doc- norepinephrine levels and state anxiety, (d) IL-2-induced NCA and emotion-focused coping, (e) IL-2-induced NCA and problem-focused coping, (f) IL-2-induced NCA and perceived control, (g) norepinephrine levels vs. perceived control, (h) IL-2 secretion and perceived control, (i) norepinephrine levels and IL-2-induced NCA and (j) epinephrine levels and IL-2 secretion. In general, correlations are done with data from both DBCP and controls, whereas correlations with perceived control (f-h) are done for DBCP only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,37 Although the association between impaired NCA and the development of breast cancer has not been established, research on humans and other species points to a significant role of NCA in preventing the development of cancer, including breast cancer, and its metastases. [1][2][3][4]8,9 Additional studies doc- norepinephrine levels and state anxiety, (d) IL-2-induced NCA and emotion-focused coping, (e) IL-2-induced NCA and problem-focused coping, (f) IL-2-induced NCA and perceived control, (g) norepinephrine levels vs. perceived control, (h) IL-2 secretion and perceived control, (i) norepinephrine levels and IL-2-induced NCA and (j) epinephrine levels and IL-2 secretion. In general, correlations are done with data from both DBCP and controls, whereas correlations with perceived control (f-h) are done for DBCP only.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] NCA has also been demonstrated to be an independent prognostic marker in patients with cancer. 8,9 Imai et al 10 showed that selected lifestyle factors, such as maintaining body weight, not smoking, increasing intake of green vegetables and moderate alcohol consumption, may have an effect on natural cytotoxicity and that NCA can be increased by altering several lifestyle factors. Other studies have shown that restricted lifestyle changes, such as increasing exercise, losing weight and reducing fat and alcohol intake, are associated with a significant reduction in breast cancer risk (reviewed by Chlebowski 11 ).…”
mentioning
confidence: 99%
“…Although it is not an endpoint, the extent of disease at initial diagnosis (i.e., number of positive nodes) is important prognostically. Levy et al (1985) found self-reports of fatigue (POMS) obtained shortly following initial treatment to be a predictor of nodal status in women with breast cancer, but there was no effect for fatigue if NK cell levels were first entered into the regression equation. We also examined disease progression to the lymph nodes in women with gynecologic cancer (Roberts et al, 1994).…”
Section: Biological Pathwaysmentioning
confidence: 99%
“…Subjects were women with cervical (Stage I, n = 27; Stage II, n = 10) or endometrial (Stage I, n = 17; Stage II, n = 4) cancer assessed on two occasions (separated by approximately one week) following their diagnosis and prior to treatment. Distress measures included selfreported distress (POMS) and interviewer-rated distress and disturbance of affect (a modified version of a Schedule for Affective Disorders and Shizophrenia-SADS; Endicott & Spitzer, 1978-interview) to address inconsistencies in previous research (e.g., Levy, Herberman, Maluish, Schlein, & Lippman, 1985). Twenty age-matched healthy women were included to validate emotional distress indicators.…”
Section: Biological Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation